Condições higiênico-sanitárias e de manejo de rebanhos leiteiros correlacionados à qualidade do leite cru refrigerado - Cortezi, Alessandra Maria [UNESP] (2014)
The objective this study was to assay 10 dairy farms that produce refrigerated raw milk, located in the southeastern of São Paulo State, on the hygenicsanitary conditions and management of the herd and, if possible, to correlate the quality of the milk produced with the standards recommended by IN62. For this, a checklist was applied together with the assessment of the rate of clinical and subclinical mastitis, identification of the microorganisms involved and their sensitivity to antimicrobials. The microbiological, physical-chemical and SCC parameters were also analyzed according to the established by law. Following application of the checklist,test of the black deep mugand CMT were performed and samples from the positive mammary quarters were collected in sterile tubes for microbiological isolation. Bulk tank milk samples were submitted to SCC, TBC and composition analysis. From 1280 mammary quarters evaluated, 43.67% were positive for the CMT, characterizing subclinical mastitis; and 2.89%, in the test of the black deep mug, characterizing clinical mastitis. Staphylococcus aureus was the most frequently isolated microorganism, and in cases of clinical mastitis, represented 64.86% of all positive samples, followed by S. epidermidis 18.91% and S. intermedius 2.70%. In cases of subclinical mastitis, S. aureus was isolated from 73.60% of the quarters examined, followed by S. epidermidis 16.57%, Corynebacterium sp. 3.66%, S. dysgalactiae 3.08%, S. intermedius 1.93%, Enterococcus sp. 0.59% and Bacillus sp. 0.58%. Regarding the in vitro antimicrobial susceptibility test, florfenicol was the antibiotic to which the microorganisms isolated in clinical mastitis cases showed higher sensitivity. Of the 10 farms milk producers seven had values higher than the 500,000 cels. / mL for SCC in relation to that established by IN62, but for TBC and protein, all attended the set of at least 300,000 CFU / mL and 2.9 g / 100g, respectively, but for ...